The impact of natural resource, information and communication technology adoption, and economic expansion on financial development in post COVID era - He, Qiao; Xie, Henglang; Zhu, Yichang; Huang, Lingyu (Elsevier, 2024)
This study explores the interplay between natural resources, economic growth, and financial development in China, extending the inquiry to the moderating role of Information and Communication Technology (ICT). Utilizing the advanced Fourier Autoregressive Distributed Lag (ARDL) framework on data spanning from 1991 to 2020, our analysis delineates the dual influence of natural resources on financial development. Results indicate that natural resources alone have a deleterious effect on financial development both in the short and long run. However, when combined with ICT, the long-run effects are positive, suggesting that ICT has a transformative potential on the natural resources-financial development nexus. Conversely, in the short run, this interaction proves detrimental. These findings underscore the imperative for a holistic strategy that harmonizes economic growth, ICT advancement, and natural resource utilization to foster sustainable financial development.